Prototype Kotak Menjaga Kekeringan Dan Kelembaban Sepatu Berbasis Mikrokontroller - Afandi, Faizal Qurnia; Bachri, Affan; Ilmi, Ulul (Faculty of Engineering, Universitas Brawijaya, 2022)
Shoes are one of the most important clothes for daily life. However, not just a season factor that affects of the problem to drying shoes when wet, could be due to the situation and conditions like in the evening that would not be possible and will not be able to find the scorching light or sunlight. Based on the problem, the author devising a shoes dryer as well as odor-causing bacterial disinfectant in shoes. The result of Prototype Box Dryer and Automatic Bacterial Disinfectant Odor Causing of Shoes in Microcontroller Based, when the power supply is given voltage then the tool will be working. How Prototype Box Dryer and Automatic Bacterial Disinfectant Odor Causing of Shoes in Microcontroller Based works : the first fan will lit up appropriate to humidity above 90%, the second fan will lit up appropriate to the temperature above 34ÂºC, heating element lit up appropriate to humidity above 90%, UV-C lamp will lit up appropriate to humidity below 89%. The result of the temperature and humidity will be showing on the LCD 16x2